Nicorandil treatment improves survival and spatial learning in aged granulin knockout mice - Niedowicz, Dana M.; Wang, Wang‐Xia; Prajapati, Paresh; Zhong, Yu; Fister, Shuling; Rogers, Colin B.; Sompol, Pradoldej; Powell, David K.; Patel, Indumati; Norris, Christopher M.; Saatman, Kathryn E.; Nelson, Peter T. (Brain pathology (Zurich, Switzerland), 2025)
Mutations in the human granulin (GRN) gene are associated with multiple diseases, including dementia disorders such as frontotemporal dementia (FTD) and limbic‐predominant age‐related TDP‐43 encephalopathy (LATE). We studied a Grn knockout (Grn‐KO) mouse model in order to evaluate a potential therapeutic strategy for these diseases using nicorandil, a commercially available agonist for the ABCC9/Abcc9‐encoded regulatory subunit of the “K+ATP” channel that is well‐tolerated in humans. Aged (13 months) Grn‐KO and wild‐type (WT) mice were treated as controls or with nicorandil (15 mg/kg/day) in drinking water for 7 months, then tested for neurobehavioral performance, neuropathology, and gene expression. Mortality was significantly higher for aged Grn‐KO mice (particularly females), but there was a conspicuous improvement in survival for both sexes treated with nicorandil. Grn‐KO mice performed worse on some cognitive tests than WT mice, but Morris Water Maze performance was improved with nicorandil treatment. Neuropathologically, Grn‐KO mice had significantly increased levels of glial fibrillary acidic protein (GFAP)‐immunoreactive astrocytosis but not ionized calcium binding adaptor molecule 1 (IBA‐1)‐immunoreactive microgliosis, indicating cell‐specific inflammation in the brain. Expression of several astrocyte‐enriched genes, including Gfap, were also elevated in the Grn‐KO brain. Nicorandil treatment was associated with a subtle shift in a subset of detected brain transcript levels, mostly related to attenuated inflammatory markers. Nicorandil treatment improved survival outcomes, cognition, and inflammation in aged Grn‐KO mice. Progranulin knockout mice display a profound reduction in survival, as well as increased inflammation and cognitive impairment. Treatment of these mice with nicorandil—a K+ATP channel agonist, decreased mortality and improves cognitive impairment.